Morality extracted under crowding impairs face identification. (June 2022) - Shirai, Risako; Ogawa, Hirokazu
We investigated whether morality associated with faces is perceptible even under less optimal visual conditions such as crowding. A facial image was paired with a sentence describing an immoral act or a neutral act. Participants imagined the person performing the actions described in the sentence during the learning phase. Then, in the crowding phase, the target face was briefly presented in the left or right peripheral visual fields. Participants were required to judge the gender or morality of the target face in Experiment 1 and to choose the target face from two faces in Experiment 2. In both experiments, flankers were presented around the target face in the flanker condition, whereas no flankers were presented in the no-flanker condition. Experiment 1 indicated that the accuracy of judgments about the morality of a crowded face was higher for immoral faces than for neutral faces. This demonstrates that morality is preferentially extracted even when conscious access to facial representations is limited. Experiment 2 showed that the accuracy of selecting the flanked face from two faces was higher for neutral faces than for immoral faces. These indicated that the morality processed under the crowding impaired the discrimination of the facial identity.